Pelatihan Pemanfaatan AI untuk Pembuatan Perangkat Pembelajaran Mendalam di SMK Satya Bhakti 1 Jakarta - Endaryono, Endaryono; Mahyudi, Mahyudi; Saputra, Aswin (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2026)
The community service program titled "Pelatihan Pemanfaatan AI untuk Pembuatan Perangkat Pembelajaran Mendalam bagi Guru-guru SMK Satya Bhakti I Jakarta" aims to enhance the capabilities of vocational school teachers in leveraging Artificial Intelligence (AI) technology to develop more effective and interactive learning tools. This training encompasses the basics of AI, the use of AI tools and platforms for creating instructional media, and the application of deep learning techniques to improve teaching quality. Participants are provided with practical guidance and examples of AI implementation in creating modules, evaluations, and teaching materials tailored to the characteristics of vocational students. This activity to boost teachers' competencies in facing modern educational challenges and provide a tangible contribution to improving the quality of learning at SMK Satya Bhakti I Jakarta. As the spearhead of the teaching and learning process, teachers can utilize AI technology to develop more diverse teaching materials, such as Semester Lesson Plans (RPS), Student Worksheets (LKPD), and instructional content. Thus, this training is intended to enhance the teaching and learning process, particularly in preparing for the implementation of deep learning in schools. The training has provided numerous benefits for teachers at SMK Satya Bhakti 1. These include: teachers starting to create their own learning videos with narration created by ChatGPT. Some teachers are creating interactive PowerPoint presentations with AI visuals and automated quizzes. The use of QR codes and interactive links in lesson plans and student worksheets is becoming common practice. Furthermore, several teachers are able to create more varied and meaningful semester and annual programs. Teachers feel more confident in facing digital learning.